If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -9) = 39 Reorder the terms: 7(-9 + x) = 39 (-9 * 7 + x * 7) = 39 (-63 + 7x) = 39 Solving -63 + 7x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '63' to each side of the equation. -63 + 63 + 7x = 39 + 63 Combine like terms: -63 + 63 = 0 0 + 7x = 39 + 63 7x = 39 + 63 Combine like terms: 39 + 63 = 102 7x = 102 Divide each side by '7'. x = 14.57142857 Simplifying x = 14.57142857
| -8p=50+q | | 5x-4y+3x-3y= | | 2=3cos(X) | | 2-3cos(x)=0 | | 2-3cosx=0 | | (9-y^2)+y=72 | | 5p=100-q(Dd) | | 3x=850 | | (72-y^2)+y=9 | | 2x^2-20x+2xy+y^2-14y+58=0 | | 4=63 | | 6x+3y=-36 | | 3.5(x-4)=4x-7 | | 28=x+4x | | 47-2x=8x+8 | | (2w+10)(2w+4)=w(w+5)+190 | | 36x= | | 13c+1=11c+9 | | x+9=16x | | (x+9)(3x-12)=0 | | 2x+2=-6+3x | | 10x-8=5x-2 | | 6y^2-32Y+32=0 | | 10x-40=-20 | | 14x+5x^2=0 | | -2(2t+6)=-36 | | (E+1)*2= | | -5(2t+9)=-75 | | 10(s-6)=-81 | | -3(2t+2)=-6 | | 2(f-10)=-12 | | 9-2=3(x+2) |